Prevalence of infectious abortion and its complications in pregnant women hospitalized in Ardabil city hospital during 2011-2018 - Jalilvand, Faranak; Farzipour, Shahla; Mohammadshahi, Jafar; Kabood Mehri, Amir (International Journal of Contemporary Pediatrics, 2021)
Background: Infectious abortion and its mortality is one of the most serious health threats to women. Infectious abortion with high prevalence rate is more accessible in many of developing countries. The aim of current study, was to investigate the prevalence of infectious abortion and its complications in pregnant women hospitalized in Ardabil city hospital during 2011-8. Methods: In this retrospective cross-sectional study which done on pregnant women with symptom of infectious abortion who admitted to Alavi hospital in Ardabil city during the years 2011-2018. Data collected by a checklist including demographic and clinical information and then analyzed by statistical methods in SPSS version 20. Results: The rate of infectious abortion in this study was 40 people per 50,000 live births. The mean age of the studied women was 32.58±5.35 years. The highest number of infectious abortion was related to the women in the gestational age group over 13 weeks (50%). Most of women with 80% had fever and 52.5% of women had an open cervix at the time of referral. Complications of infectious abortion included peritonitis, uterine rupture, septic shock, and DIC. Conclusions: Results showed that the rate of infectious abortion in this study was 22.5% that generally due to manipulation by methods such as curettage, drug use and its side-effects. By considering the average age of women about 32 years and problems related about pregnancy, so programing and training in this themes could prevent many of these problems in pregnant women in future.